Superparamagnetic CuFeO2 Nanoparticles in Deep Eutectic Solvent: an Efficient and Recyclable Catalytic System for the Synthesis of Imidazo[1,2-a]pyridines - Lu, Jun; Li, Xiao-Tang; Ma, Er-Qian; Mo, Li-Ping; Zhang, Zhan-Hui (ChemCatChem, 2014)
Superparamagnetic CuFeO2 nanoparticles were prepared and characterized by XRD, SEM, TEM, FRIR spectroscopy, and vibrating sample magnetometry techniques. The catalytic activity of CuFeO2 nanoparticles was investigated in the one‐pot, three‐component reaction of 2‐aminopyridines, aldehydes, and alkynes using citric acid–dimethylurea melt as a green solvent. An array of imidazo[1,2‐a]pyridines were obtained in good to excellent yields. The catalytic system can be successfully reused six times with keeping its catalytic performance. Green solvent and efficient catalyst: A recyclable catalytic system comprising magnetically recoverable CuFeO2 nanoparticles in a citric acid–dimethylurea melt is established as an efficient and environmentally friendly system for the one‐pot synthesis of imidazo[1,2‐a]pyridines.